(untitled) (Nigerian Journal of Physiological Sciences, 2021)
In Africa traditional medicine, certain plant leaves are employed in the treatment of metabolic disorders such as dyslipidaemia. Telfairia occidentalis is named among Nigerian plants that are under investigation for anti-hyperlipidemic activity. The antihperlipidemic and antioxidant potentials of Telfairia Occidentalis (TO) aqueous leaf extract were studied in male Sprague- Dawley rats. Twenty-four healthy male Sprague-Dawley rats were grouped into four of six rats thus: Group A (control) received normal saline (10mg/Kg); treated groups B, C and D, received, 50mg/kg; 100mg/kg; and 150mg/kg of Telfairia occidentalis aqueous leaf extract for 14 days respectively. At the end of the experiment serum cholesterol (CHOL), triglyceride (TG), high density lipoprotein (HDL) and low density lipoprotein (LDL) were determined. Liver enzymes’ aspartate amino transferase (AST), alanine amino transferase (ALT), Alkaline phosphatase (ALP) were also assessed. Serum level creatinine was determined and antioxidant enzymes’ reduced glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) were investigated. Lipid peroxidation’s malonaldehyde (MDA) level was also assessed. Results from the current study showed a significant decrease in CHOL and LDL levels at all the doses tested (p<0.05) compared with control. Telfairia occidentalis produced a significant increase (p<0.05) in HDL level in all the tested doses compared with control However, TG was significantly decreased at 100mg and 150mg/kg compared with control (p<0.05). TO aqueous leaf extract produced a significant decrease (p<0.05) in AST level in all the tested doses compared with control. ALT level was significantly decreased (p<0.05) at 100mg/kg and 150mg/kg doses compared with control while ALP level significantly elevated (p<0.05) in all the doses tested compared with control. Creatinine level was significantly reduced at 50mg/kg and 100mg/kg doses when compared with control (p<0.05). The results from the antioxidant analysis revealed a significant increase in SOD, GSH and CAT with concomitant reduction in MDA’s lipid peroxidation when compared with control (p<0.05). The current findings revealed that Telfairia occidentalis aqueous leaf extract is anti-hyperlipidemic, possesses hepato-reno effect and antioxidant potentials. However, care has to be taken during its use as it has ability to elevate LDL and the activities of liver enzymes at higher doses which may be deleterious to the body system.